2016
DOI: 10.1007/s11127-016-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

Public–private political cleavage: what happens after retirement?

Abstract: Political preferences of public employees differ from those of workers in the private sector. The former are more likely to vote for left-wing parties and orient themselves ideologically towards the left. This political cleavage can be understood as the result of occupational incentives, or alternatively, as ideological self-selection whereby individuals favoring government solutions seek employment in the public sector. We test the selection hypothesis by estimating the effects of public versus private occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…One reason for the difference is that professional background determines socioeconomic conditions and may thus shape identity (Braendle and Stutzer 2016). Consistent with this, public sector employees seem to be politically more active (Bhatti and Hansen 2012) and lean more to the left ideologically (Knutsen 2005; Jensen, Sum, and Flynn 2009; Rattsø and Sørensen 2016). They may also be relatively unwilling to support market-oriented solutions, and thus, a smaller public sector.…”
Section: Theory and Hypothesesmentioning
confidence: 63%
See 1 more Smart Citation
“…One reason for the difference is that professional background determines socioeconomic conditions and may thus shape identity (Braendle and Stutzer 2016). Consistent with this, public sector employees seem to be politically more active (Bhatti and Hansen 2012) and lean more to the left ideologically (Knutsen 2005; Jensen, Sum, and Flynn 2009; Rattsø and Sørensen 2016). They may also be relatively unwilling to support market-oriented solutions, and thus, a smaller public sector.…”
Section: Theory and Hypothesesmentioning
confidence: 63%
“…This raises the obvious question of why municipal employees’ information advantage leads to increased—and not to decreased—spending and only in their own sector of employment. These results also speak against the interpretation that municipal employees increase spending because they generally prefer a larger public sector (Knutsen 2005; Jensen, Sum, and Flynn 2009; Rattsø and Sørensen 2016). Finally, we would like to point out that intraparty bargaining—for which we already provided support earlier—is an example of an indirect mechanism that could generate the observed sector specific effects: Given that councilors with municipal employment cannot be members of the subcommittee of their own sector, they have to influence sector-specific spending indirectly.…”
Section: Resultsmentioning
confidence: 85%
“…Public-sector employees turn out to vote more, even after controlling for their socio-demographic and attitudinal characteristics (Corey and Garand, 2002). Moreover, the policy preferences of public employees change after retirement, converging with the preferences of non-public-sector workers (Rattsø and Sørensen, 2016). This finding clearly challenges the assumption that the higher turnout rate among public employees is only due to a ‘selection bias’ in their recruitment, whereby individuals having distinct political preferences and being more likely to vote are attracted to public-sector jobs.…”
Section: On the Political Behaviour Of Public Employeesmentioning
confidence: 99%
“…Most articles that systematically study this premise have, however, not fared well. Most of the studies within this subfield have not found any meaningful difference between publicly and privately employed, and even there the effects were limited to specific countries and sectors of the publicly employed (Blais and Dion, 1991;Garand et al, 1991;Goul Andersen, 1992;Svallfors, 1997;Dolan, 2002;Rattsø and Sørensen, 2016). This is quite surprising given the central role of this idea in the literature on support for the welfare state.…”
Section: Introductionmentioning
confidence: 99%